If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4a + 4b + 4c)(4a + 4b + 4c) = 0 Multiply (4a + 4b + 4c) * (4a + 4b + 4c) (4a * (4a + 4b + 4c) + 4b * (4a + 4b + 4c) + 4c * (4a + 4b + 4c)) = 0 ((4a * 4a + 4b * 4a + 4c * 4a) + 4b * (4a + 4b + 4c) + 4c * (4a + 4b + 4c)) = 0 Reorder the terms: ((16ab + 16ac + 16a2) + 4b * (4a + 4b + 4c) + 4c * (4a + 4b + 4c)) = 0 ((16ab + 16ac + 16a2) + 4b * (4a + 4b + 4c) + 4c * (4a + 4b + 4c)) = 0 (16ab + 16ac + 16a2 + (4a * 4b + 4b * 4b + 4c * 4b) + 4c * (4a + 4b + 4c)) = 0 Reorder the terms: (16ab + 16ac + 16a2 + (16ab + 16bc + 16b2) + 4c * (4a + 4b + 4c)) = 0 (16ab + 16ac + 16a2 + (16ab + 16bc + 16b2) + 4c * (4a + 4b + 4c)) = 0 (16ab + 16ac + 16a2 + 16ab + 16bc + 16b2 + (4a * 4c + 4b * 4c + 4c * 4c)) = 0 (16ab + 16ac + 16a2 + 16ab + 16bc + 16b2 + (16ac + 16bc + 16c2)) = 0 Reorder the terms: (16ab + 16ab + 16ac + 16ac + 16a2 + 16bc + 16bc + 16b2 + 16c2) = 0 Combine like terms: 16ab + 16ab = 32ab (32ab + 16ac + 16ac + 16a2 + 16bc + 16bc + 16b2 + 16c2) = 0 Combine like terms: 16ac + 16ac = 32ac (32ab + 32ac + 16a2 + 16bc + 16bc + 16b2 + 16c2) = 0 Combine like terms: 16bc + 16bc = 32bc (32ab + 32ac + 16a2 + 32bc + 16b2 + 16c2) = 0 Solving 32ab + 32ac + 16a2 + 32bc + 16b2 + 16c2 = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '16'. 16(2ab + 2ac + a2 + 2bc + b2 + c2) = 0 Ignore the factor 16.Subproblem 1
Set the factor '(2ab + 2ac + a2 + 2bc + b2 + c2)' equal to zero and attempt to solve: Simplifying 2ab + 2ac + a2 + 2bc + b2 + c2 = 0 Solving 2ab + 2ac + a2 + 2bc + b2 + c2 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 86=-5-7(-4n-5) | | 30+50x=65x | | 17.42(p)=8.71 | | 4.13-0.54x=5x-2.795 | | 2w+8x-15y+7w+7x+8y= | | 3(1+-0.5y)+4y=-7 | | 5x+4y+9=0 | | x+16-64= | | x*(3x)^1/2 | | 3C^3-24= | | 2x-7/3=-3 | | 2x-7/7=-3 | | x-4/4=9 | | ((7x-1)^(1/2))^2 | | -3/42-x/53/4 | | 5x-20=-3x+68 | | 3y=(x-20) | | 61000+1.30x=19x | | 0.43=x*0.24 | | 1/5=2/3×w | | 1100+0.06x=0.11x | | 2x+6=3x+31 | | sin(x)=-0.48 | | 3h+10=13 | | 60=5x-100 | | 2x+9=5x-19 | | 4(x-9)-3(2x+5)=4.5(2x-15) | | 4(x-5)-3(2x+9)=1.5(2x-9) | | 0.5x-2(x-1)=-1.5x+2 | | y=32x-16x^2 | | 2.3(7-x)=-0.9(9-x) | | 3x+29=12-79 |